Religion and professional experience: Are they predictors of nurses’ spiritual intelligence? Cross-sectional study - Jhon Alex Zeladita-Huaman; Juana Matilde Cuba-Sancho; Martha Brigida Martina-Chávez; Roberto Zegarra-Chapoñan; Henry Castillo-Parra (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to analyze the relationship between religion and professional experience with spiritual intelligence in nurses Methods: cross-sectional and analytical study carried out in 2021, with the participation of 544 nursing professionals working in health facilities in Peru during the COVID-19 pandemic. Multiple regression analysis and Pearson’s correlation were used to analyze the data. Results: in nurses, a healthy level of spiritual intelligence predominated (42.8%). Those who did not profess a religion were more likely to have a lower spiritual intelligence score (global scale and dimensions); however, experienced nurses were more likely to have higher spiritual intelligence (global scale and dimensions) than novice nurses (p<0.05). Conclusions: spiritual intelligence in nurses was predicted by religion and professional experience. This finding suggests that spiritual intelligence in nursing is consolidated through religious practices and during professional practice.